Historia Zimowej Szkoły Leśnej – podsumowanie czternastu sesji konferencji z okazji jubileuszu piętnastolecia ZSL - Siebyła, Marta; Gil, Wojciech (Leśne Prace Badawcze, 2025)
The article is a summary of fourteen sessions of the Winter Forest School (ZSL) organized by the Forest Research Institute in cooperation with the Directorate General of the State Forests. The initiator of the ZSL was professor Andrzej Klocek – Director of the Forest Research Institute in the years 1990–2008. According to the professor, the purpose of the conference – Winter Forest School – was to create an international and independent forum for the presentation of problems that are important now and in the foreseeable future, as well as the approach to their solutions at the both on a national and international level. Another important goal was to integrate the community of researchers and forestry practitioners in Poland. The article summarizes on the basis of data from fourteen sessions in the analysis of the personnel composition of the existing organizational structures of the ZSL, the topics undertaken, the number of participants, speakers, lectures and publications delivered. The Winter Forest School, which has been organized regularly since 2009, provides a platform for the exchange of knowledge and professional experience between foresters, scientists, natural scientists and entrepreneurs. Well-known and respected scientists and practitioners from Poland and abroad take part in the ZSL, and their papers are published by the IBL in the form of books. A total of 369 papers were delivered in all sessions, including more than 70 from abroad, and the total number of the ZSL participants amounted to 3436 people.